Whole-body cryotherapy in athletes - Banfi, G.; Lombardi, G.; Colombini, A.; Melegati, G. (Sports Medicine, 2010)
Cold therapy is commonly used as a procedure to relieve pain symptoms, particularly in inflammatory diseases, injuries and overuse symptoms. A peculiar form of cold therapy (or stimulation) was proposed 30 years ago for the treatment of rheumatic diseases. The therapy, called whole-body cryotherapy (WBC), consists of exposure to very cold air that is maintained at -110°C to -140°C in special temperature-controlled cryochambers, generally for 2 minutes. WBC is used to relieve pain and inflammatory symptoms caused by numerous disorders, particularly those associated with rheumatic conditions, and is recommended for the treatment of arthritis, fibromyalgia and ankylosing spondylitis. In sports medicine, WBC has gained wider acceptance as a method to improve recovery from muscle injury. Unfortunately, there are few papers concerning the application of the treatment on athletes. The study of possible enhancement of recovery from injuries and possible modification of physiological parameters, taking into consideration the limits imposed by antidoping rules, is crucial for athletes and sports physicians for judging the real benefits and/or limits of WBC.